2013
DOI: 10.3390/v5010241
|View full text |Cite
|
Sign up to set email alerts
|

Arenavirus Variations Due to Host-Specific Adaptation

Abstract: Arenavirus particles are enveloped and contain two single-strand RNA genomic segments with ambisense coding. Genetic plasticity of the arenaviruses comes from transcription errors, segment reassortment, and permissive genomic packaging, and results in their remarkable ability, as a group, to infect a wide variety of hosts. In this review, we discuss some in vitro studies of virus genetic and phenotypic variation after exposure to selective pressures such as high viral dose, mutagens and antivirals. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 182 publications
(180 reference statements)
0
54
0
3
Order By: Relevance
“…The selection of changes varies with each host, suggesting that the virus sequence adapts to a specific host molecule (Table 4). Changes in GP were very close to the cleavage site (residue 260) (18), changes in NP were either close to the ssRNA binding site (residue 171) in the N domain or close to the immune evasion and Z protein binding sites (residues 59, 223, 341, and 551) in the C domain (18), and changes in L were close to the endonuclease domain (residue 266) or to the globular domain (1572). Protein prediction analysis showed that those mutations, at the amino acid level, induced structural changes in GP and NP (18).…”
Section: Resultsmentioning
confidence: 99%
“…The selection of changes varies with each host, suggesting that the virus sequence adapts to a specific host molecule (Table 4). Changes in GP were very close to the cleavage site (residue 260) (18), changes in NP were either close to the ssRNA binding site (residue 171) in the N domain or close to the immune evasion and Z protein binding sites (residues 59, 223, 341, and 551) in the C domain (18), and changes in L were close to the endonuclease domain (residue 266) or to the globular domain (1572). Protein prediction analysis showed that those mutations, at the amino acid level, induced structural changes in GP and NP (18).…”
Section: Resultsmentioning
confidence: 99%
“…Los análisis filogenéticos a partir de las secuencias en estudio indicaron que los virus del género Arenavirus se agruparon formando dos clados independientes constituidos por, al menos, 25 especies, y por los virus del serocomplejo Tacaribe y Lassa-coriomeningitis linfocítica, lo cual coincide con lo evidenciado por Zapata, et al (5). En el árbol se observa que las secuencias de Sincelejo conformaron un grupo monofilético con altos valores de soporte de la rama, cuyo ancestro común está relacionado con el ancestro que dio origen a los LCMV, lo cual demuestra la identidad de estos virus.…”
Section: Discussionunclassified
“…Estos agentes se han clasificado de acuerdo con sus propiedades antigénicas, en dos grupos: el complejo serológico Tacaribe, el cual incluye virus autóctonos del Nuevo Mundo, y el complejo serológico LassaCoriomeningitis Linfocítica, conformado por virus autóctonos de África y por el virus de la coriomeningitis linfocítica (LCMV), conocidos como el grupo del Viejo Mundo (3)(4)(5).…”
unclassified
“…Animals were defined as having reached terminal points either when their body weight decreased by Ͼ30% compared to a nomogram or if the rectal temperature fell below 38°C in addition to body weight loss. Statistical analyses of the survival curves were performed using the log-rank (Mantel-Cox) 2 test and/or the Fisher's exact test. The statistical significance of duration of fever was analyzed using the Student t test.…”
Section: F F L L L C G G R S C T M G Q I V T M F F E a L L P H I I I mentioning
confidence: 99%
“…A renaviruses can cause neurologic or hemorrhagic fever diseases in humans, and few preventive or therapeutic measures are available (1,2). The most significant arenavirus pathogen is Lassa fever virus (LASV), which causes infections that are endemic to many countries in West Africa, with an estimated 500,000 cases resulting in ϳ5,000 deaths annually (3).…”
mentioning
confidence: 99%